Strategic management (second edition) - Mohamed, Zainal Abidin; Ho, Jo Ann; Wong, Foong Yee (Oxford Fajar, 2014)
The second edition of Strategic Management caters for Business Administration and Management undergraduates, as well as postgraduates. The book is designed to be used as a capstone course after the students have been exposed to the various functional areas of management. It is also useful for practitioners and general readers who seek essential knowledge on strategic management. Spanning 12 chapters, the book covers topics such as a brief historical background on strategic planning, the elements of strategic planning, and the strategic planning process of evaluation and formulation that includes various models used by diverse companies. Unlike most other strategic management course books, this book also discusses the action plan as part of the implementation phase, besides the strategic planning system. A new chapter has been added to keep in touch with current developments, especially in the pursuance of competitive advantage. The book presents content in an accessible manner, complemented by localized examples and scenarios. Each chapter ends with a summary and discussion questions, and the book conludes with six real and comprehensive case studies. These cases enable students to link the knowledge they have acquired to the real world. They can also be used by trainers in their training sessions and by those who believe in the effectiveness of the case approach.